Will robot replace workers? Assessing the impact of robots on employment and wages with meta-analysis - Dario Guarascio; Alessandro Piccirillo; Jelena Reljic (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
This study conducts a meta-analysis to assess the effects of robotization on employment and wages, compiling data from 33 studies with 644 estimates on employment and a subset of 19 studies with 195 estimates on wages. We identify a publication bias towards negative outcomes, especially concerning wages. After correcting for this bias, the actual impact appears minimal. Thus, concerns about the disruptive effects of robots on employment and the risk of widespread technological unemployment may be exaggerated or not yet empirically supported. While this does not preclude that robots will be capable of gaining greater disruptive potential in the future or that they are not already disruptive in specific contexts, the evidence to date suggests their aggregate effect is negligible.
Keywords: J21; J23; J24; J31; O33; 330; robots; employment; wages; meta-analysis; publication bias